MATINYA PESANTREN DI KOTA PEKALONGAN - Nurkhamidi, Aris (Jurnal Penelitian, 2010)
The existence and contribution of Islamic boarding school (pesantren) for Indonesian people is significance enough. Pesantren is an educational and community development institution. Its existence in Pekalongan, however, is in serious condition. Today, its development is less maximal, the increase of student amount is not significance, the Islamic classical book study does not improve, and the institution is stagnant, i.e. as a religious learning place only. There are some pesantrens that their student amount become more in a little calculation every years, and even their students are off, and only few pesantrens develop bigger. This research describes that condition and government take a strategic initiative to reinforce their existence and vitality